Biodiversity Conservation in Relation to Plants Used for Medicines and Other Products in Indonesia - Kuswata Kartawinata (Journal of Tropical Ethnobiology, 2004)
Biological diversity, or biodiversity, refers to all organisms occurring on Earth. Biodiversity is a manifestation of biochemical diversity and can be viewed at three levels: ecosystem, species and genetic. Indonesia has one of the richest endowments of biodiversity — at all levels -- of all countries in the world; it is often referred to as a "megadivenifyr country. Plant diversity in Indonesia encompasses more than 30,000 species of ferns and flowering plants distributed over a wide range of ecosystems, ranging from mangrove swamps in coastal areas to tropical forests in the lowland and mountain regions to low scrub areas and grasslands at high elevations. Many plant species in Indonesia have high genetic diversity as well. Of the 30,000 known species, only a fraction -- about 1000 -- has been recorded as being useful for medicinal purposes. There has been considerable evidence that Indonesia's plant diversity is decreasing at an alarming rate. It is imperative, therefore, that we intensively explore, collect, study and identify additional plants that may provide new drugs, before the resources are lost forever. This effort must be broad-based, encompassing ethnobotanical, taxonomic, phytochernical, chemosysternatic, random and ecopharmacognosic approaches. Studies based on leads provided by herbalists and folk medicine practitioners should be one important area of focus. Conservation of biodiversity is crucial in part because a diverse array of plants (and other organisms) is needed for human well-being, by providing food, shelter and medicines. For this reason, biodiversity conservation must be balanced with utilization. Local people have extensive knowledge of many uses of bind iversity. Access to this traditional knowledge and to genetic materials and biochemical resources should be compensated and intellectual property rights should be protected.